The Trigemino-Cardiac Reflex: Beyond the Diving Reflex - Tumul Chowdhury (Frontiers Research Topics, 2018)
The trigemino-cardiac reflex (TCR) is a well established brain-stem reflex and commonly manifests as bradycardia, asystole, hypotension and / or apnea. This phenomenon was extensively explored in the recent past. However, the area related to its exact bio-physiological mechanism, neuro-anatomical linkages, clinical implications, its role in non neurological events and future directions should need to be further investigated. Therefore, this present research topic on TCR would mainly focus on various aspects of TCR and present a comprehensive and exhaustive overview about a phenomena that gains more and more interest during the last few years. Our goal is to present models about the different aspects of the TCR to develop in-depth understanding of TCR.